EFFECT OF RABBIT MANURE AND NPK INTAN SUPER COMPOUND FERTILIZER ON GROWTH AND YIELD OF STRINGBEAN (Phaseolus vulgaris L.) - Parbin Lestober Pasaribu; Syafrizal Hasibuan; Lokot Ridwan Batubara (Bernas : Jurnal Penelitian Pertanian, 2018)
This research was conducted in Experimental Garden of Faculty of Agriculture University of Asahan, Kisaran Timur Sub-district of Asahan Regency, North Sumatera Province with flat tofografi located at an altitude of ± 15 m above sea level. the research time was carried out from June to July 2017. This research was arranged based on Factorial Randomized Block Design with 2 treatment factors and 3 replications. The first factor is the provision of rabbit manure (K)with 3 levels ie: K0 = 0 kg / plot, K1 = 1.44 kg / plot, and K2 = 2.88 kg / plot. The second factor is the application of NPK Intan Super Compound fertilizer application, with 4 levels ie N0 = 0 g / plot, N1 = 7.2 g / plot, N3 = 14.4 g / plot and N3 = 21.6 g / plot. The results of rabbit manure showed the best treatment with a dose of 2.88 kg / plot (K2) resulted in plant length 171,98 cm, leaf area 585,04 cm, pod length per plant 13,71 cm and production per plot 594,58 g. Giving of NPK compound fertilizer showed the best treatment that is with dose 21,6 g / plot (N3) yielding plant length 174,88 cm, leaf area 572,39 cm, length of pod 13,33 cm and production per plot 561,111g. The interaction of rabbit manure and NPK compound fertilizer on growth and yield of stringbean showed no significant effect on all parameters observed.